Prenatal Exposure to NO(2) and Ultrasound Measures of Fetal Growth in the Spanish INMA Cohort - Iñiguez, Carmen (Environ Health Perspect, 2015)
BACKGROUND: Air pollution exposure during pregnancy has been associated with impaired fetal growth. However, few studies have measured fetal biometry longitudinally, remaining unclear as to whether there are windows of special vulnerability. OBJECTIVE: The aim was to investigate the impact of nitrogen dioxide (NO(2)) exposure on fetal and neonatal biometry in the Spanish INMA study. METHODS: Biparietal diameter (BPD), femur length (FL), abdominal circumference (AC), and estimated fetal weight (EFW) were evaluated for up to 2,478 fetuses in each trimester of pregnancy. Size at 12, 20, and 34 weeks of gestation and growth between these points, as well as anthropometry at birth, were assessed by SD scores derived using cohort-specific growth curves. Temporally adjusted land-use regression was used to estimate exposure to NO(2) at home addresses for up to 2,415 fetuses. Associations were investigated by linear regression in each cohort and subsequent meta-analysis. RESULTS: A 10-μg/m(3) increase in average exposure to NO(2) during weeks 0–12 was associated with reduced growth at weeks 0–12 in AC (–2.1%; 95% CI: –3.7, –0.6) and EFW (–1.6%; 95% CI: –3.0, –0.3). The same exposure was inversely associated with reduced growth at weeks 20–34 in BPD (–2.6%; 95% CI: –3.9, –1.2), AC (–1.8%; 95% CI: –3.3, –0.2), and EFW (–2.1%; 95% CI: –3.7, –0.2). A less consistent pattern of association was observed for FL. The negative association of this exposure with BPD and EFW was significantly stronger in smoking versus nonsmoking mothers. CONCLUSIONS: Maternal exposure to NO(2) in early pregnancy was associated with reduced fetal growth based on ultrasound measures of growth during pregnancy and measures of size at birth. CITATION: Iñiguez C, Esplugues A, Sunyer J, Basterrechea M, Fernández-Somoano A, Costa O, Estarlich M, Aguilera I, Lertxundi A, Tardón A, Guxens M, Murcia M, Lopez-Espinosa MJ, Ballester F, on behalf of the INMA Project. 2016. Prenatal exposure to NO(2) and ultrasound measures of fetal growth in the Spanish INMA Cohort. Environ Health Perspect 124:235–242; http://dx.doi.org/10.1289/ehp.1409423